DETERMINANTS TO HOMEOWNERSHIP AND/OR LEASING INTENTIONS: A REVIEW AND PROPOSED FRAMEWORK - William Wee-Lim Hew; Cheng Ling Tan; Sook Fern Yeo, (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
The contribution the housing and construction sector makes to the national economy is closely tied to new project launches in the country. At present, nations are suffering from a global economic slowdown and a slumping property market. Governments and private developers have even initiated many affordable housing projects, but interestingly these units are not as popular as expected. Many housing projects across the world are initiated without a clear understanding of the needs and behavioural tendencies of homebuyers. The ability to understand homebuyers' behaviour is limited due to the lack of sufficient research using a concise and all-encompassing framework that is supported by a strong theoretical foundation. A thorough review and comparison of three fields of psychology found environmental psychology to be suitable and Mehrabian and Russell's (1974) theory to be relevant, and ought to be complemented with the theory of planned behaviour (TPB). A framework is proposed, positing that favourable evaluations of the environment (residential environment) and social factors (attitude, subjective norms, perceived behavioural control) will elicit favourable emotional states (pleasure, arousal, dominance/place attachment) which in turn lead to favourable behavioural response (homeownership intention). On the other hand, should the evaluations of the environment and social factors be unfavourable, this would lead to unfavourable emotions and subsequently unfavourable behavioural response (leasing intention).